KMCanvas study in the mining sector: Knowledge management with a focus on kaizen (Advances in Knowledge Representation, 2022)
Knowledge management involves the process of collecting, processing and disseminating the knowledge possessed by the company, with the aim of transforming itself into a more intelligent and competitive organization. Thus, this research sought to evaluate the results of the KMCanvas study focusing on the Kaizen continuous improvement tool in a knowledge management project in the mining sector. In the field research, a workshop was held to present KMCanvas and, after guidance, selected employees from two companies in the mining sector were asked to implement the model focused on Kaizen in a knowledge management project in organizations. Then, semi-structured interviews were carried out to identify the information for the satisfactory development of Kaizen activities with KMCanvas. As a result, the present research proved that KMCanvas is applicable to the reality of organizations, since it presents knowledge dissemination practices in a simple way and shows itself as an innovative choice to achieve competitive advantages.